Pemetaan Peak Ground Acceleration di Daerah Nangroe Aceh Darussalam Menggunakan Data Hasil Rekaman Sinyal Seismik - Hafidzi, Aldyan; Suarbawa, Komang Ngurah; Astra, Made Kris Adi (Universitas Hamzanwadi, 2023)
The region of Nangroe Aceh Darussalam is a region with a high frequency of earthquake due to the location where the two biggest tectonic plates meet which is the Eurasia and Indo-Australia. This research is done to map the PGA using the digital signal processing method from seismic wave recording of the earthquake that happened in Beureun County on 7th of December 2016. The result is the highest PGA is from Banda Aceh Station with the value of 0,258 gal while the lowest PGA measured is from Sinabang island station with 0,014 gal